(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Thermoplastic materials such as polypropylene (PP) are ideal candidates to be used as power cable insulation materials. However, the mechanical properties of PP, which is brittle and stiff, need to be modified to meet the requirements of power cable insulation applications. To overcome this, ethylene-propylene-diene monomer (EPDM) can be melt blended with PP to improve PP’s mechanical properties. In the current work, the effect of blending different contents of EPDM with PP was investigated in terms of the morphology, chemical structure, dielectric response, electrical, and mechanical properties. The results show that the EPDM blended well with the PP as the EPDM dispersed in the PP structure. Meanwhile, the chemical structure and dielectric response of the EPDM and PP blend became slightly different with high contents of EPDM, which subsequently affected the breakdown strength and mechanical properties. Nevertheless, it is worth noting that PP blended with low contents of EPDM has the potential to be used as recyclable power cable insulation materials.